Investigation of Pollution Status in River No. 2, Freetown, Sierra Leone, Using Physicochemical and Bacterial Indicators - Yahaya Kudush Kawa; Gibrilla Thullah; Sam Sonny Tommy; Victoria Olufemi Danke Kawa (International Journal of Pollution: Prevention & Control, 2026)
This study assessed the physicochemical and bacteriological quality of surface water in the River No. 2 watershed, Sierra Leone, through monthly sampling from March–August 2024 at upstream, midstream, and downstream sites. Analyses included temperature, turbidity, pH, electrical conductivity, total dissolved solids, ammonia, fluoride, sulfite, nitrate, lead, arsenic, chromium, and microbial indicators (Escherichia coli, fecal and non-fecal coliforms). Most physicochemical parameters met WHO drinking-water guidelines. pH (7.0–7.3), TDS (7–17 mg/L), turbidity (0–3 NTU), ammonia, nitrate, and sulfite were within acceptable limits. However, chromium (up to 0.70 mg/L) and fluoride (up to 2.5 mg/L) exceeded WHO standards at some locations, indicating localized contamination. Lead and arsenic were not detected. Water Quality Index (WQI) results varied by method. The Weighted Arithmetic WQI classified the water as very poor to unfit for drinking (244.5–458.9), while CCME WQI scores (79.3–89.9) indicated “Good” upstream and midstream conditions and “Fair” downstream quality. This discrepancy reflects differences in index sensitivity. Fecal and non-fecal coliforms were detected, though E. coli was absent, suggesting no recent fecal pollution. Overall, the river is suitable for several uses, but elevated fluoride and chromium require targeted intervention and continued monitoring.
Keywords: Freetown; Water monitoring; microbial assessment; physicochemical; river no. 2 catchment